Ivor horton's beginning Visual C++ 2013 - Horton, Ivor (Wrox, a Wiley brand, 2014)
Horton's unique tutorial approach and step-by-step guidance have helped over 100,000 novice programmers learn C++. In Ivor Horton's Beginning Visual C++ 2013, Horton not only guides you through the fundamentals of the standard C++ language, but also teaches you how C++ is used in the latest Visual Studio 2013 environment. Visual Studio 2013 includes major changes to the IDE and expanded options for C++ coding. Ivor Horton's Beginning Visual C++ 2013 will teach you the latest techniques to take your Visual C++ coding to an all-new level.